Brief program notes for a saxophone lecture recital: compositions by Benjamín Gutiérrez, Fernande Decruck, Karel Husa and Robert Muczynski - Vargas Gamboa, Nosara (Kansas State University, 2021)
The repertoire selected for this Master of Music lecture recital represents a variety of musical styles composed by composers of diverse backgrounds. Each selection discussed is considered a significant piece of saxophone literature for a variety of reasons. Composer Benjamin Gutiérrez was born in 1937 and is a highly respected and successful Costa Rican composer. Rapsodia para Saxofón Alto y Orquesta was composed in 1974. This work represents the first major classical saxophone piece ever written by a Costa Rican composer. The piece is dedicated to Costa Rican classical saxophone pioneer Norman Calderón. Fernande Decruck, born in France in 1896, was a female composer who studied at the Paris Conservatory. Her major works for saxophone were primarily dedicated to French saxophone pioneer Marcel Mule, including her Sonate en Ut# pour Saxophone Alto et Orchestre which was composed in 1943. Karel Husa, a world renown composer and Pulitzer Prize winner, was born in 1921 in the Czech Republic. He passed away in 2016 in the United States. Husa had a very successful career in France as a composer and as a conductor. His passion, however, was composition. He taught composition at Cornell University and spent the remainder of his life in America leaving behind a legacy of highly regarded compositions. Élégie et Rondeau pour Alto Saxophone et Orchestre was premiered by German and American saxophone pioneer Sigurd Raschèr. Robert Muczynski was a prominent American composer and pianist who was born in Chicago in 1929. He was a talented musician and composer who worked with numerous musicians who commissioned pieces from him due to his national and international successes. The Sonata for Alto Saxophone and Piano, Op. 29 represents one of his commissioned pieces. The composition was commissioned by saxophonist Trent Kynaston, who asked Muczynski to compose a piece to be premiered at the 2nd World Saxophone Congress in Chicago in 1970. Since its premiere, the Sonata has become part of the standard classical saxophone repertoire.
Keywords: Saxophone; Benjamin Gutierrez; Fernande Decruck; Karel Husa; Robert Muczynski